1989
DOI: 10.1093/tropej/35.2.60
|View full text |Cite
|
Sign up to set email alerts
|

Specific Antibodies in Colostrum of North Indian Mothers with Special Reference to Their Nutritional Status

Abstract: The anti-S. typhi antibody is predominantly IgA class, and the anti-polio-antibody, antimeasles antibody, anti-E. Coli enterotoxin antibody and anti-S. typhi agglutinins were found adequate in the colostrum samples of well- and under-nourished mothers. No antibody against tetanus toxin was detectable in colostrum samples from mothers of both the groups, although they have been immunized against tetanus toxoid during pregnancy, suggesting thereby that the presence of specific antibody in the mother's breast sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
3
1
Order By: Relevance
“…Results of several studies supported this species‐specificity finding, where the levels of colostral and milk immune components was found to be independent of maternal characteristics such as nutritional status, age, income, parity, and gestational age 13,15,33,35,36,38 . However, some investigations report an influence of maternal characteristics on the colostral and milk constituents 18,20,39 . In the present study, analyses of one‐way anova and Pearson’s correlation coefficients showed that maternal characteristics of the postpartum mother did not have any correlation with the immunoglobulin in colostrums.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Results of several studies supported this species‐specificity finding, where the levels of colostral and milk immune components was found to be independent of maternal characteristics such as nutritional status, age, income, parity, and gestational age 13,15,33,35,36,38 . However, some investigations report an influence of maternal characteristics on the colostral and milk constituents 18,20,39 . In the present study, analyses of one‐way anova and Pearson’s correlation coefficients showed that maternal characteristics of the postpartum mother did not have any correlation with the immunoglobulin in colostrums.…”
Section: Discussionsupporting
confidence: 84%
“…13,15,33,35,36,38 However, some investigations report an infl uence of maternal characteristics on the colostral and milk constituents. 18,20,39 In the present study, analyses of one-way anova and Pearson's correlation coefficients showed that maternal characteristics of the postpartum mother did not have any correlation with the immunoglobulin in colostrums. This confers species-specifi city in production of colostrum and milk, 37 and corresponds to the fi ndings reported elsewhere.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Garg and co-workers also found colostrum to contain antibodies against measles (Garg, Thirupuram and Saha, 1988;Garg et al, 1989).…”
Section: N Rizvimentioning
confidence: 93%
“…The protein component of colostrum consists primarily of enzymes, antiinfective agents, hormones, and growth factors, many of which serve to support neonatal growth and development (Kunz et al, 1999;Xu, 1996). Of these bioactive agents, immune cells, such as antibodies (e.g., secretory IgA, IgG, IgM) make up the largest fraction of total protein content of colostrum (Garg et al, 1989;Hartmann et al, 1985). Other compounds include still more antimicrobial factors (e.g., oligosaccharides, fatty acids), antiinflammatory agents, transporters (e.g., lactoferrin), digestive enzymes, and peptide hormones (Baumrucker and Blum, 1993; reviewed by Kunz et al, 1999).…”
mentioning
confidence: 99%